Topographical Evaluation of Penile Lichen Sclerosus Reveals a Lymphocytic Depleted Variant, Preferentially Associated With Neoplasia: A Report of 200 Cases. (August 2020) - Piris, Adriano; Sanchez, Diego F.; Fernandez-Nestosa, Maria José; Cañete-Portillo, Sofía; Campagnoli, Tania; Gonzalez Stark, Lorena; Zarza, Patricia; Oneto, Sabrina; Lezcano, Cecilia; Rodriguez, Ingrid; Velazquez, Elsa F.; Mihm, Martin; et al.
Since the seminal study of Hart and Helwig in 1975, there are few detailed pathological studies of lichen sclerosus (LS). The aims of this study were to provide a detailed histopathological description of penile LS, as well as to explore its relationship with penile intraepithelial neoplasia (PeIN) or invasive carcinoma. We evaluated 200 patients and designed a topographical approach for the histological evaluation focusing in alterations of the following anatomical layers: squamous epithelium, lamina propria, dartos, and corpus spongiosum. We documented the quantity and topographical location of stromal lymphocytes. The prevalent lesions found were epithelial hyperplasia, atrophy, PeIN, basal cell vacuolization, lamina propria sclerosis, and variable patterns of lymphocytic infiltration. Various unique patterns of stromal sclerosis were described: perivascular, globular, linear, and solid fibrosis/hyalinization; any of them were found to be diagnostic for LS. The variation in the topography and density of lymphocytes was determinant for the identification of LS morphological variants: lichenoid, band-like, lymphocytic depleted, and mixed. A major finding was the identification of the variant designated as lymphocytic depleted LS, which we considered as the morphological prototype of LS associated with penile neoplasia. The detailed description of this complex lesion presented in this study may help pathologists in practice to identify and better define LS. The identification of the special variants suggests a role of the stromal lymphocytes in the process of carcinogenesis. Confirmation of the observations with more studies is necessary to determine the significance of these findings.